2016
DOI: 10.1002/jemt.22682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with simvastatin on bone microarchitecture of the femoral head in an osteoporosis animal model

Abstract: The objective of this study was to evaluate the microarchitecture and trabecular bone strength at the distal region of the femur, and its biomechanical properties with simvastatin administration with two different doses in ovariectomized (OVX) rats. Ninety rats were divided into six groups to evaluate treatment with the simvastatin drug (n = 15): SH (Sham surgery), SH-5 (5 mg simvastatin), SH-20 (20 mg simvastatin), OVX, OVX-5, and OVX-20. Euthanasia was performed at three different times, five animals per per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
11
0
3
Order By: Relevance
“…The lovastatin dose used in this study does not exceed the recommended statin dose for high-intensity hypocholesterolemic effects in humans (80 mg/day) [ 36 ]. Monteiro et al showed that oral supplementation of very-high-dose simvastatin (20 mg/kg/day, equivalent to 140 mg/day in humans) improved the bone microstructure of ovariectomized rats in 14 days [ 37 ]. Similar effects were not observed with a lower dose within the same treatment period [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lovastatin dose used in this study does not exceed the recommended statin dose for high-intensity hypocholesterolemic effects in humans (80 mg/day) [ 36 ]. Monteiro et al showed that oral supplementation of very-high-dose simvastatin (20 mg/kg/day, equivalent to 140 mg/day in humans) improved the bone microstructure of ovariectomized rats in 14 days [ 37 ]. Similar effects were not observed with a lower dose within the same treatment period [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monteiro et al showed that oral supplementation of very-high-dose simvastatin (20 mg/kg/day, equivalent to 140 mg/day in humans) improved the bone microstructure of ovariectomized rats in 14 days [ 37 ]. Similar effects were not observed with a lower dose within the same treatment period [ 37 ]. Thus, it is reasonable that lovastatin at the dose used in the current study produced no effects on bone dynamic histormorphometric parameters in ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were numbered and randomly divided into two groups: Veh group (n=90) received Polyethylene Glycol 400 (All Chemistry; São Paulo, SP, Brazil) at 0.5 mg/kg body weight (vehicle), and S group (n=90) received Simvastatin (Medley; Campinas, SP, Brazil) at 0.5 mg/kg body weight orally 18 . Administrations were daily performed in a single dose, starting 24 h before induction of PD and maintained until the end of the respective periods of euthanasia.…”
Section: Methodsmentioning
confidence: 99%
“…A quantificação de trabeculado ósseo por Tricromo de Masson foi expresso em Pixel² (ISSA et al, 2015;MONTEIRO et al, 2016), a quantificação por picro-sirius red foi expresso em porcentagem de colágeno total (%) (PEREIRA, B. F. et al, 2014) e a imunomarcação por TRAP foi expresso em Escores (SHIMANO, R. C. et al, 2014).…”
Section: Apresentação Dos Resultados Para Cada Análiseunclassified
“…A qualidade óssea é determinada pela taxa de remodelação óssea que é um processo contínuo de renovação óssea, onde um tecido velho ou danificado é reabsorvido e um novo tecido é formado, mantendo assim a integridade mecânica do osso e a homeostase do cálcio no organismo. As propriedades estruturais dos ossos incluem sua geometria (tamanho e forma) e sua microarquitetura (trabecular ou cortical), enquanto suas propriedades materiais (ISSA et al, 2015;MACEDO et al, 2017;MONTEIRO et al, 2016;VOLPON;LIMA, 2008;SHIMANO, ROBERTA CARMINATI et al, 2014).…”
Section: Análisesunclassified